Molecular Genetic Analysis of PKHD1 Mutations in Pedigrees With Autosomal Recessive Polycystic Kidney Disease (Iranian Journal of Kidney Diseases, 2018)
Introduction. A wide variety of mutations are spread throughout the PKHD1 gene, which encodes a 4074-bp amino acid protein, namely fibrocystin/polyductin, and is responsible for all features of autosomal recessive polycystic kidney disease (ARPKD). Autosomal recessive polycystic kidney disease is a hereditary early-onset form of polycystic kidney disease characterized by fusiform dilation of collecting ducts and congenital hepatic fibrosis. The highest level of PKDH1 expression is in the kidneys of fetus and adults, suggesting the functionally importance of the gene in the mature kidney in addition to its role in kidney development. Materials and Methods. Mutational analysis of the PKHD1 gene was performed in 11 families with a history of 1 to 6 fetuses or children affected by ARPKD, which either were aborted or died shortly after birth. Analyses were done using the Next Generation sequencing and Sanger sequencing techniques. Results. Four novel mutations, including c.6469C>T, c.9218 G>A, c.10456T>C, and c.8863C>G, and 3 previously reported ones, including c.9524A>G, c.1095G>A, c.1123C>T, were identified. Conclusions. In view of high consanguineous marriages in Iranian population, the frequency of disease is expected to be higher than the world average.